2017
DOI: 10.1007/s00198-017-3953-z
|View full text |Cite
|
Sign up to set email alerts
|

Post-fracture care: do we need to educate patients rather than doctors? The PREVOST randomized controlled trial

Abstract: A patient-centered care program with a dedicated case manager can significantly improve post-fracture BMD investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…A total of 4199 unique records (citations) were identified with the literature search strategies, of which 43 met inclusion criteria . A flow diagram of the literature search and inclusion/exclusion process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 4199 unique records (citations) were identified with the literature search strategies, of which 43 met inclusion criteria . A flow diagram of the literature search and inclusion/exclusion process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Significance of meta‐analysis findings sensitive to removal of Gardner et al, Kessous et al, or Merle et al studies in influence analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been increasing recognition of the need for patient education regarding secondary prevention following a fracture . Langer and colleagues recently surveyed more than 1000 patients and even among patients rated high risk for secondary fracture using the Fracture Risk Assessment Tool (FRAX) tool, most perceived their future fracture risk as low.…”
Section: Discussionmentioning
confidence: 99%
“…Patient education and counselling were shown to improve post-fracture care and treatment initiation, with more controversial results on medication adherence. As a prominent example for post-fracture care, the PREVOST trial suggested that repeated oral and written information about fragility fractures and osteoporosis management by a case manager increased treatment initiation (53% initiated post-fracture care in the intervention compared to 33% in the control) [66]. In another study [67], patient education and referral to endocrinologist by a nurse was shown to improve the initiation of calcium and vitamin D, although up to 50% of patients with osteoporosis did not complete follow-up visits and/or did not adhere to treatment recommendations for osteoporosis.…”
Section: Recommendations For Practicementioning
confidence: 99%